Regulation of chemicals demands assessment of risks rather than identification of hazards only - P. Marx-Stoelting; V. Ritz; M. Herzler; C. Kneuer; K. Aiello-Holden; S Brescia; S. E. Escher; S. Feustel; E. Fritsche; J. Gebel; E. F. Kenny; R. Landsiedel; et al. (Archives of Toxicology, 2026)
This position paper was collaboratively written during the international expert symposium “EU Chemicals Assessment - Risk- or Hazard-based?” that was organised by the German Federal Institute for Risk Assessment (BfR) in Berlin on November 27th and 28th 2025. Twenty experts from several institutions and European countries considered the scientific merits of both hazard-based and risk-based approaches to chemical safety assessment. While hazard information is essential, it does not reflect real-world exposure conditions that determine the likelihood of harm. On balance, we support a risk-based approach because it enables more proportionate, transparent and scientifically grounded regulatory decisions.

P28-27 Developmental Neurotoxicity as a Case Example for a Six-Step Framework for the Sustainable Regulatory Implementation of NAMs - J. Blum; K. Bartmann; J. de Paula Souza; E. Fritsche (Toxicology Letters, 2025)

P18-67 Regulation of key neurodevelopmental processes by disease pathways and nuclear receptors in a human Neurosphere Assay - E. Kuchovska; K. Koch; K. Bartmann; K. Schluppmann; A. Donmez; J. Klose; G. Raad; M. Schade; L.-C. Saborowski; E. Fritsche (Toxicology Letters, 2025)

P18-65 Advancing the Grouping and Harmonization of Similar Key Events in the AOP Wiki: Ontology-Based Key Event Component Combinations as Catalysts for Integration - J. Filipovska; K. Audouze; J. Blum; L.-A. Clerbaux; E. Coerek; E. Demuynck; S. Edwards; E. Fritsche; L. Gerner; K. Groh; G. Hench; N. Jeliazkova; et al. (Toxicology Letters, 2025)

P18-51 Advancing in vitro Developmental Neurotoxicity (DNT) screening: Expanding the biological coverage of the DNT in vitro battery (IVB) by integration of glial cell-related endpoints - A.S. Cheruvil lilikumar; E. Zühr; R. Guzzo; E. Fritsche; K. Koch (Toxicology Letters, 2025)

P30-79 Bridging Mechanistic Neurotoxicity Testing and Regulatory Application with Human-Relevant NAMs within CHIASMA - R. Roy Chowdhury; I. Scharkin; E. Fritsche; K. Koch (Toxicology Letters, 2025)

P30-76 Linking hormone receptor signaling to neurodevelopmental disruption: Advancing EDC hazard assessment using human-based DNT in vitro models - K. Koch; K. Schlüppmann; L.M. Stark; A. Dönmez; E. Fritsche (Toxicology Letters, 2025)

P30-70 Application of human-based 2D and 3D new approach methodologies for assessing developmental and adult neurotoxicity (DNT and ANT) in vitro - J. Klose; K. Bartmann; F. Bendt; A. Dönmez; K. Koch; E. Zuehr; A. Mosig; E. Fritsche (Toxicology Letters, 2025)

P28-04 Towards Animal-Free DIT Testing: Establishing a Human Stem Cell-Based Assay for Early Hematopoiesis - C. Spruck; A. Bartel; G. Brockerhoff; S. Fayyaz; Q. Li; F.A. Grimm; E. Fritsche; K. Koch; J. Tigges (Toxicology Letters, 2025)

P14-15 Species-, Cell Type- and Developmental-Specific Variability in DNA Repair Capacities of Human and Rodent Neural Progenitor Cells - L.P. Czernik; M. Pahl; L. Dittmann; E.R. de Caro; L.M. Stark; E. Fritsche; J. Tigges; K. Koch (Toxicology Letters, 2025)

Deciphering the genetic basis of salinity tolerance in a diverse panel of cultivated and wild soybean accessions by genome-wide association mapping - Rajat Pruthi; Chanderkant Chaudhary; Sandeep Chapagain; Mostafa Mohamed Elbasuoni Abozaid; Prabhat Rana; Ravi Kiran Reddy Kondi; Roberto Fritsche-Neto; Prasanta K. Subudhi (Theoretical and Applied Genetics, 2024)
Key message In a genome-wide association study involving 269 cultivated and wild soybean accessions, potential salt tolerance donors were identified along with significant markers and candidate genes, such as GmKUP6 and GmWRKY33 . Abstract Salt stress remains a significant challenge in agricultural systems, notably impacting soybean productivity worldwide. A comprehensive genome-wide association study (GWAS) was conducted to elucidate the genetic underpinnings of salt tolerance and identify novel source of salt tolerance among soybean genotypes. A diverse panel comprising 269 wild and cultivated soybean accessions was subjected to saline stress under controlled greenhouse conditions. Phenotypic data revealed that salt tolerance of soybean germplasm accessions was heavily compromised by the accumulation of sodium and chloride, as indicated by highly significant positive correlations of leaf scorching score with leaf sodium/chloride content. The GWAS analysis, leveraging a dataset of 32,832 SNPs, unveiled 32 significant marker-trait associations (MTAs) across seven traits associated with salt tolerance. These markers explained a substantial portion of the phenotypic variation, ranging from 14 to 52%. Notably, 11 markers surpassed Bonferroni’s correction threshold, exhibiting highly significant associations with the respective traits. Gene Ontology enrichment analysis conducted within a 100 Kb range of the identified MTAs highlighted candidate genes such as potassium transporter 6 ( GmKUP6 ), cation hydrogen exchanger ( GmCHX15 ), and GmWRKY33 . Expression levels of GmKUP6 and GmWRKY33 significantly varied between salt-tolerant and salt-susceptible soybean accessions under salt stress. The genetic markers and candidate genes identified in this study hold promise for developing soybean varieties resilient to salinity stress, thereby mitigating its adverse effects.

P09-21 Oligodendrocyte development as a crucial key event for developmental neurotoxicity - E. Fritsche; K. Koch (Toxicology Letters, 2024)

OS04-05 Addressing uncertainties in the DNT in vitro battery (DNT IVB) by incorporating glial models and increasing human relevance - K. Koch; E. Zühr; K. Bartmann; R. Guzzo; A.S. Cheruvil Lilikumar; L. Stark; I. Egger; O. Myhre; E. Fritsche (Toxicology Letters, 2024)

OS02-03 Using a systems biology approach to construct adverse outcome pathway networks aligned with the FAIR principles - L. Ladeira; A. Mazein; M. Ostaszewski; A. Verhoeven; E. Kuchovská; J. Sanz-Serrano; A. Drees; K. Reiche; K. Sewald; E. Fritsche; M. Vinken; L. Geris; et al. (Toxicology Letters, 2024)

OS01-06 Human-based New Approach Methodologies for developmental and adult neurotoxicity testing in vitro - K. Bartmann; F. Bendt; A. Dönmez; J. Klose; K. Koch; E. Fritsche (Toxicology Letters, 2024)

S05-01 Functional mapping of neurodevelopmental disorders to ontology-based DNT NAMs for Next Generation Risk Assessment of chemicals - E. Kuchovska; L. Ladeira; K. Bartmann; D. Polozij; N. Gorts; E. Corek; A. Donmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; A. Gamba; et al. (Toxicology Letters, 2024)

P22-35: Mapping of DNT NAMs’ signaling pathways in human physiology and disease for regulatory application - E. Kuchovska; K. Bartmann; L. C. Maia Ladeira; A. Dönmez; L.-C. Saborowski; F. Bendt; M. Schade; G. Raad; R. Lesage; A. Gamba; B. Staumont; L. Geris; et al. (Toxicology Letters, 2023)

P21-14: Neurodevelopmental toxicity of T-2 mycotoxin in human-based primary and induced pluripotent stem cell-derived neural progenitor cells in 3D and 2D - M. Taroncher Ruiz; J. Kapr; K. Bartmann; J. Tigges; Y. Rodriguez-Carrasco; M.J. Ruiz; E. Fritsche (Toxicology Letters, 2023)

P16-40: Metabolic effects and half-life of organophosphate and pyrethroid pesticides and their metabolites in HepaRG cells - K. Fritsche; D. Lichtenstein; C. Muñoz; M. Garí; K. Abass; J.O. Grimalt; A. Braeuning (Toxicology Letters, 2023)

P16-10: Refinement of an in vitro testing battery for developmental neurotoxicity assessment by integration of radial glia- and astrocyte-specific endpoints - E. Zühr; K. Koch; E. Fritsche (Toxicology Letters, 2023)

P16-08: Development of the NPC1_RAR_GR assay to identify putative endocrine disrupting chemicals (EDCs) disturbing glucocorticoid receptor (GR) or retinoic acid receptor (RAR) signaling in vitro - K. Schlüppmann; S. Hüsken; L. Stark; A. Dönmez; N. Förster; K. Koch; E. Fritsche (Toxicology Letters, 2023)

P09-34: Unraveling hormonal dependencies and associated species-specificities of neurodevelopmental key events to improve EDC risk assessment - K. Koch; K. Schlüppmann; S. Hüsken; L. Stark; S. Masjosthusmann; J. Klose; N. Förster; A. Dönmez; E. Fritsche (Toxicology Letters, 2023)

Docosahexaenoic Acid (DHA) Supplementation Alters Phospholipid Species and Lipid Peroxidation Products in Adult Mouse Brain, Heart, and Plasma - Grace Y. Sun; Michael K. Appenteng; Runting Li; Taeseon Woo; Bo Yang; Chao Qin; Meixia Pan; Magdalena Cieślik; Jiankun Cui; Kevin L. Fritsche; Zezong Gu; Matthew Will; et al. (NeuroMolecular Medicine, 2021)

Minimum Selenium Requirements Increase When Repleting Second-Generation Selenium-Deficient Rats but Are Not Further Altered by Vitamin E Deficiency - Roger A. Sunde; Kevin M. Thompson; Kevin L. Fritsche; Jacqueline K. Evenson (Biological Trace Element Research, 2017)

The Power of Bioenergy‐Related Standards to Protect Biodiversity - K. J. HENNENBERG; C. DRAGISIC; S. HAYE; J. HEWSON; B. SEMROC; C. SAVY; K. WIEGMANN; H. FEHRENBACH; U. R. FRITSCHE (Conservation Biology, 2010)
The sustainable production of bioenergy is vital to avoiding negative impacts on environmental goods such as climate, soil, water, and especially biodiversity . We propose three key issues that should be addressed in any biodiversity risk‐mitigation strategy: conservation of areas of significant biodiversity value; mitigation of negative effects related to indirect land‐use change; and promotion of agricultural practices with few negative impacts on biodiversity. Focusing on biodiversity concerns, we compared principles and criteria set to address biodiversity and other environmental and social issues in seven standards (defined here as commodity‐based standards or roundtables, or relevant European legislation): five voluntary initiatives related to bioenergy feedstocks, the Renewable Transport Fuel Obligation (United Kingdom), and the European Renewable Energy Source Directive. Conservation of areas of significant biodiversity value was fairly well covered by these standards. Nevertheless, mitigation of negative impacts related to indirect land‐use change was underrepresented. Although the EU directive, with its bonus system for the use of degraded land and a subquota system for noncrop biofuels, offered the most robust standards to mitigate potential negative effects, all of the standards fell short in promoting agricultural practices with low negative impacts on biodiversity. We strongly recommend that each standard be benchmarked against related standards, as we have done here, and that efforts should be made to strengthen the elements that are weak or missing. This would be a significant step toward achieving a bioenergy industry that safeguards Earth's living heritage .

Cone visual pigments and retinal mosaics in the striped marlin - K. A. Fritsches; L. Litherland; N. Thomas; J. Shand (Journal of Fish Biology, 2003)
Three different cone photoreceptor visual pigments in the retina of striped marlin Tetrapturus audax were found with the aid of microspectrophotometry. This provides the first evidence for the basis of colour vision in the Istiophoridae. Furthermore, regional variations in photoreceptor density, type and spatial arrangement indicate differing visual capabilities along different visual axes.

Maximum rates of N 2 fixation and primary production are out of phase in a developing cyanobacterial bloom in the Baltic Sea - J. R. Gallon; A. M. Evans; D. A. Jones; P. Albertano; R. Congestri; B. Bergman; K. Gundersen; K. M. Orcutt; K. von Bröckel; P. Fritsche; M. Meyerhöfer; K. Nachtigall; et al. (Limnology and Oceanography, 2002)
Although N 2 ‐fixing cyanobacteria contribute significantly to oceanic sequestration of atmospheric CO 2 , little is known about how N 2 fixation and carbon fixation (primary production) interact in natural populations of marine cyanobacteria. In a developing cyanobacterial bloom in the Baltic Sea, rates of N 2 fixation (acetylene reduction) showed both diurnal and longer‐term fluctuations. The latter reflected fluctuations in the nitrogen status of the cyanobacterial population and could be correlated with variations in the ratio of acetylene reduced to 15 N 2 assimilated. The value of this ratio may provide useful information about the release of newly fixed nitrogen by a cyanobacterial population. However, although the diurnal fluctuations in N 2 fixation broadly paralleled diurnal fluctuations in carbon fixation, the longer‐term fluctuations in these two processes were out of phase.

Prey capture and accommodation in the sandlance, Limnichthyes fasciatus (Creediidae; Teleostei) - J. D. Pettigrew; S. P. Collin; K. Fritsches (Journal of Comparative Physiology A, 2000)

Novel bacterial endosymbionts of Acanthamoeba spp. related to the Paramecium caudatum symbiont Caedibacter caryophilus - Matthias Horn; Thomas R. Fritsche; Romesh K. Gautom; Karl‐Heinz Schleifer; Michael Wagner (Environmental Microbiology, 1999)
Acanthamoebae are increasingly being recognized as hosts for obligate bacterial endosymbionts, most of which are presently uncharacterized. In this study, the phylogeny of three Gram‐negative, rod‐shaped endosymbionts and their Acanthamoeba host cells was analysed by the rRNA approach. Comparative analyses of 16S rDNA sequences retrieved from amoebic cell lysates revealed that the endosymbionts of Acanthamoeba polyphaga HN‐3, Acanthamoeba sp. UWC9 and Acanthamoeba sp. UWE39 are related to the Paramecium caudatum endosymbionts Caedibacter caryophilus, Holospora elegans a n d Holospora obtusa . With overall 16S rRNA sequence similarities to their closest relative, C. caryophilus , of between 87% and 93%, these endosymbionts represent three distinct new species. In situ hybridization with fluorescently labelled endosymbiont‐specific 16S rRNA‐targeted probes demonstrated that the retrieved 16S rDNA sequences originated from the endosymbionts and confirmed their intracellular localization. We propose to classify provisionally the endosymbiont of Acanthamoeba polyphaga HN‐3 as ‘ Candidatus Caedibacter acanthamoebae’, the endosymbiont of Acanthamoeba sp. strain UWC9 as ‘ Candidatus Paracaedibacter acanthamoebae’ and the endosymbiont of Acanthamoeba sp. strain UWE39 as ‘ Candidatus Paracaedibacter symbiosus’. The phylogeny of the Acanthamoeba host cells was analysed by comparative sequence analyses of their 18S rRNA. Although Acanthamoeba polyphaga HN‐3 clearly groups together with most of the known Acanthamoeba isolates (18S rRNA sequence type 4), Acanthamoeba sp. UWC9 and UWE39 exhibit Acanthamoeba isolates. Therefore, we propose two new sequence types (T13 and T14) within the genus Acanthamoeba containing, respectively, Acanthamoeba sp. UWC9 and Acanthamoeba sp. UWE39.

Mineralization of 2-amino-4,6-dinitrotoluene by manganese peroxidase of the white-rot fungus Nematoloma frowardii - K. Scheibner; M. Hofrichter; W. Fritsche (Biotechnology Letters, 1997)